MOUSE COMPLEMENT: THE EFFECT OF SEX HORMONES AND CASTRATION ON TWO OF THE LATE-ACTING COMPONENTS - Churchill, Winthrop H. (The Rockefeller University Press, 1967)
The titer of late-acting complement components in sera from male mice is 8–10 times higher than the titer of sera from female mice. Using assays developed to measure the serum content of two of the late-acting components, we have shown that this difference is due to the effect of androgen and estrogen on these two late-acting complement components. These two components have been tentatively identified as C'5 and C'6. Androgen and estrogen have greater effect on C'6 than on C'5. The possibility has not been excluded that still other of the late-acting complement components are affected by androgens and estrogens. The course of homograft rejection was unchanged in mice deficient in C'5 and C'6.